Study protocol for a randomised controlled trial of carvedilol versus variceal band ligation in primary prevention of variceal bleeding in liver cirrhosis (CALIBRE trial). Issue 1 (25th April 2019) - Tripathi, Dhiraj; Hayes, Peter Clive; Richardson, Paul; Rowe, Ian; Ferguson, James; Devine, Peter; Mathers, Jonathan; Poyner, Christopher; Jowett, Sue; Handley, Kelly; Grant, Margaret; Slinn, Gemma; et al.
Abstract : Introduction: Liver cirrhosis is the fifth largest cause of adult deaths, and a major complication, variceal bleeding is associated with a 1-year mortality of 40%. There is uncertainty on the first-line therapy for prevention of variceal bleeding owing to a lack of adequately powered trials comparing non-selective beta blockers, in particular carvedilol, with variceal band ligation. Methods and analysis: CALIBRE is a multicentre, pragmatic, randomised controlled, open-label trial with an internal pilot. The two interventions are carvedilol 12.5 mg od or variceal band ligation (VBL). Patients with liver cirrhosis and medium to large oesophageal varices that have never bled are eligible for inclusion. The primary outcome is any variceal bleeding within 1 year of randomisation. Secondary endpoints include time to variceal bleed, mortality, transplant-free survival, adverse events, complications of cirrhosis, health-related quality of life, use of healthcare resources, patient preference and use of alternative or crossover therapies. The sample size is 2630 patients over a 4-year recruitment period, across 66 hospitals in the UK. Ethics and dissemination: The study has been approved by a National Health Service (NHS) Research Ethics Committee (REC) (reference number 18/NE/0296). The results of this trial will be submitted for publication in a peer reviewed journal. Participants will be informed via a link to a preview of the publication. A lay summary will also be provided via email or posted to participants prior to publication (ISRCTN reference number: 73887615).